Determinants of Audit Quality in Food and Beverage Companies: The Role of Audit Tenure and Auditor Reputation - Dui Rafika Ramadhani (Journal of Principles Management and Business, 2026)
This study examines the effect of audit tenure and auditor reputation on audit quality using panel data analysis. The study aims to provide empirical evidence on whether prolonged auditor-client relationships and auditor reputation influence audit outcomes. The findings reveal that audit tenure has a negative and significant effect on audit quality, indicating that longer auditor engagement may reduce independence and compromise audit quality. In contrast, auditor reputation shows no significant effect, suggesting that reputation alone does not guarantee higher audit quality. Simultaneously, both variables significantly influence audit quality, with the model explaining 57.95% of its variation. These results imply that regulators and firms should carefully consider auditor rotation policies to maintain auditor independence and improve audit quality. This study contributes to the audit literature by providing evidence from panel data analysis on the relative importance of auditor tenure and reputation in determining audit quality.